ANALISIS TERHADAP FAKTOR YANG BERPENGARUH DALAM PENYUSUNAN LAPORAN PERTANGGUNGJAWABAN DI KABUPATEN SARMI, PROVINSI PAPUA - Mardiana Dimo (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2020)
The purpose of this study is to analyze the factors that influence the presentation of the Accountant Treasury Accountability Report. Three factors are predicted to influence namely HR competency, education and training, and SIMDA implementation. The study was conducted in Sarmi Regency, Papua Province, with a population of expenditure treasurers in 35 Regional Apparatus Organizations (OPD). The research sample of 70 people. The sample method used is Porposive Sampling. The results of the study used Multiple Regression. The results of the study explained that partially HR competency factors had no significant effect, while the other two factors namely education and training, and SIMDA Implementation had a positive effect. Simultaneously these three factors have a positive and significant effect.